THE SCOPE OF THE SUBJECTS OF SOCIAL NETWORKS AND THEIR LEGAL STATUS (World Bulletin of Management and Law, 2023)
In this article analyzed the scope of the subjects of social networks and their legal status. In addition, since social network, such as Facebook or Telegram, has gained popularity in all parts of the world, the issue of giving legal status to the subjects of social network has become a big issue among legal scholars. In this article, the scope of the subjects of social networks and their legal status will be analyzed and necessary proposals will be made by the author to solve the problem. As a result of these analyses, the author can give several suggestions and recommendations for the development of the legislation of social media law